The normalisation of Food Aid: What happened to feeding people well? [version 2; peer review: 4 approved] - Robbie Davison; Martin Caraher (Emerald Publishing, 2019)
In the UK, food poverty has increased in the last 15 years and the food aid supply chain that has emerged to tackle it is now roughly 10 years old. In this time, we have seen the food aid supply chain grow at a rate that has astounded many.  Recently that growth has been aided by a grant of £20m from a large supermarket chain. It appears institutionalisation is just around the corner, if not already here. It also appears that there is far greater emphasis on dealing with  the symptoms as opposed to solving the root causes of the problem. As an opinion piece, this paper reflects on some of the prevalent issues, and suggests some ways forward.